2010
DOI: 10.14710/jitaa.35.1.34-41
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Lignocellulose Degrading Bacteria Isolated From Buffalo and Horse Gastrointestinal Tract and Elephant Dung for Feed Fiber Degradation

Abstract: Lignin is limiting factor for cellulose and hemicellulose degradation in rumen. Isolation and selection bacteria from buffalo and horse gastrointestinal tract and elephant dung could be found bacteria that have superiority to degrade lignin, xylan, and cellulose. Those animals were chosen because they were herbivores that consume low quality crude fiber as their main energy sources. Lignocellulose degrading bacteria were isolated by Hungate selective media, by using lignin (tannic acid), xylan, and cellulose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 6 publications
(9 reference statements)
0
16
0
1
Order By: Relevance
“…In the present study, 32 bacterial strains were isolated from cow dung, among which three (designated as AS1, AS2, and AS3) were efficient producer of extracellular cellulases as observed by clear hydrolysis zones after Congo red staining. Similarly, lignocellulolytic bacteria were reported from goat's feces . Aerobic bacterial strains (AS1, AS2, and AS3) were Gram positive and rod shaped and showed positive tests for oxidase, catalase, nitrate reduction, and bile esculin and negative for KOH, citrate utilization, and V–P reaction, whereas strain AS1 gave the positive test for urease in contrast to AS2 and AS3 (Table ).…”
Section: Resultsmentioning
confidence: 78%
“…In the present study, 32 bacterial strains were isolated from cow dung, among which three (designated as AS1, AS2, and AS3) were efficient producer of extracellular cellulases as observed by clear hydrolysis zones after Congo red staining. Similarly, lignocellulolytic bacteria were reported from goat's feces . Aerobic bacterial strains (AS1, AS2, and AS3) were Gram positive and rod shaped and showed positive tests for oxidase, catalase, nitrate reduction, and bile esculin and negative for KOH, citrate utilization, and V–P reaction, whereas strain AS1 gave the positive test for urease in contrast to AS2 and AS3 (Table ).…”
Section: Resultsmentioning
confidence: 78%
“…Also, the habitat of bacteria covers different environmental niches, which favors the existence of versatile strains such as thermophiles [12], psychrophiles, alkaliphiles, and acidophiles. The culturable cellulase producing bacteria have been isolated from the variety of sources such as composting heaps, decaying agricultural wastes, the feces of cow [13] and elephant, gastrointestinal tract of buffalo and horse [14], soil, and extreme environments like hot-springs [15]. Cellulose degrading bacteria play an important role in energy supply for forage animals.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose degrading bacteria play an important role in energy supply for forage animals. Wahyudi et al [14] and Varga and Kovler [16] have reported that the feed fibers were not completely converted to animal product in intensive animal farming, and 20–70% undigested cellulose was carried out with feces. Some studies have explained that the crude fiber degradation in gut is not optimal, and the fiber content of feces is still high [17], which can be utilized efficiently by microbes present in the feces of the herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…S. marcescens isolated from soil exhibited cellulase activity (Sethi et al 2013). E. casseliflavus/ gallinarum species isolated from buffalo's and horse's cecum and buffalo's colon were able to degrade lignin, xylan and cellulose, respectively (Wahyudi et al 2010). Y. pestis, pathogenic to human and other animals, has also been reported as cellulase producer (uniport data bank).…”
Section: Resultsmentioning
confidence: 99%